2006
DOI: 10.1080/00071660600756071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aflatoxin B1and fumonisin B1on body weight, antibody titres and histology of broiler chicks

Abstract: 1. Our objective was to evaluate the toxic effects of aflatoxin B1 (AFB1) and fumonisin B1 (FB1), administered singly or in combination to broilers. 2. Feeds were prepared with concentrations equal to 0, 50 and 200 microg AFB1/kg, and/or 0, 50 and 200 mg FB1/kg, and offered to broiler chicks from 8 to 41 d of age. The experimental design was totally randomised, in a 3 x 3 factorial arrangement with 9 treatments and 12 birds per treatment. Animals were vaccinated against Newcastle disease on d 14 of life and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
63
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 29 publications
12
63
1
7
Order By: Relevance
“…In consistent with our finding, in some of studies [25,26] chicks received aflatoxin treated ration had lower geometrical mean antibody titers against the Newcastle disease as compared to the control. Antibody titer against NDV significantly increased in group fed diet containing savory alone as compared with the control group.…”
Section: Discussionsupporting
confidence: 81%
“…In consistent with our finding, in some of studies [25,26] chicks received aflatoxin treated ration had lower geometrical mean antibody titers against the Newcastle disease as compared to the control. Antibody titer against NDV significantly increased in group fed diet containing savory alone as compared with the control group.…”
Section: Discussionsupporting
confidence: 81%
“…Xu et al (2011) reported that corn with low nutritional quality affected growth performance due to the presence of mycotoxins and FB1 significantly decreased body weight and feed intake and caused poor feed efficiency in broilers and turkeys. Tessari et al (2006) observed that the dietary contamination with AFB1 and FB1, individually or in combination (at 50 mg/kg and 200 mg/kg, respectively), may adversely affect the body weight, liver structure, and immune responses of broilers. …”
Section: Resultsmentioning
confidence: 99%
“…The isolation of Fusarium verticillioides and Fusarium proliferatum and the co-occurrence of fumonisins in the same substrate, especially in corn, which is the main feedstuff of poultry feeds, have frequently been reported in literature (Espada et al, 1994, Broomhead et al, 2002Tessari et al, 2006;Tessari et al, 2010). Therefore, the objective of the present study was to evaluate the performance and nutrient metabolizability in broilers fed diets containing corn contaminated with FB1 and with the addition of EGM.…”
Section: Performance and Nutrient Metabolizability In Broilers Fed DImentioning
confidence: 99%
“…Among them, AFB 1 is the most toxic for most animal species (Leeson et al, 1995;Celik et al, 2000). The toxic effects of AFs in poultry have been widely investigated (Giambrone et al, 1978;Celik et al, 1996;Sur & Celik, 2003) and are a major concern in poultry production because of serious economic losses resulting from anorexia, poor feed utilization, decreased body weight gain, decreased egg production, increased susceptibility to microbial and unspecified diseases and increased mortality (Qureshi et al, 1998;Tessari et al, 2006;Oguz, 2011).…”
Section: Introductionmentioning
confidence: 99%